2004
DOI: 10.1111/j.1469-0691.2004.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a dot-blot enzyme immunoassay (Directigen RSV) for the antigenic detection of respiratory syncytial virus from nasopharyngeal aspirates of paediatric patients

Abstract: This study investigated the efficacy of a commercial enzyme immunoassay (Directigen RSV, ColorPAC) in comparison with the shell vial culture method (using Hep-2 cells) for the detection of respiratory syncytial virus (RSV) in nasopharyngeal aspirates from children with bronchiolitis. During the period 1995-2002, 4950 samples were examined. RSV was detected in 1660 (33.5%) samples, with a sensitivity of 80.9%, a specificity of 97.5%, a positive predictive value of 93.8%, a negative predictive value of 91.6%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…In addition, other studies conducted on larger numbers of pediatric specimens using rapid ICA yielded relative indices for sensitivity ranging from 71.0% to 89.2% (Aldous et al 2004, Reina et al 2004, Zheng et al 2004, which agree with the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, other studies conducted on larger numbers of pediatric specimens using rapid ICA yielded relative indices for sensitivity ranging from 71.0% to 89.2% (Aldous et al 2004, Reina et al 2004, Zheng et al 2004, which agree with the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Neither blood contamination nor high viscosity was observed in these samples, and no other cross reactivity-inducing factors in ICA-BD could be elucidated. By using an immunomembrane filter-based rapid test, Reina et al (2004) found that 0.25% of all samples (representing 0.7% of HRSV-positive NPA) were true false-positives. On the other hand, two samples that were tested negative by RT-PCR were tested positive by both IFA and ICA-BD, presumably due to inhibition of polymerization during PCR process- ing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common laboratory method for rapid detection of RSV includes rapid antigen (enzyme immunoassay) assays produced by multiple manufacturers, with various sensitivities of 57 to 98% and specificities between 70 and 100% (1,5,10,11,13,16,20). Other diagnostic tests include culture (routine tissue culture and shell vial culture), with sensitivities between 70 and 80% and specificities of 100% (10,11,19), and direct fluorescent antigen detection, with sensitivities between 93 and 100% and specificities of 95 to 100% (1,10,16). More recently, real-time RT-PCR assays have been described as demonstrating sensitivities of 73 to 97% and specificities of 64 to 99% (7,9,11).…”
mentioning
confidence: 99%